Environmental Vulnerability and Governance in the Red River Delta: Analysis and Strategic Recommendations - Hoang Bao Tram Nguyen; Do Ngan Thao (E3S Web of Conferences)
This study examines the complex interplay between environmental vulnerability and governance structures in Vietnam’s Red River Delta, drawing comparative insights from Japan’s environmental management practices. Through a qualitative approach combining expert interviews, policy analysis, and case studies, we assess the current state of environmental governance in the delta and identify key vulnerabilities. Our findings reveal multifaceted challenges, including climate-related risks such as flooding and sea-level rise, alongside non-climate threats like industrial pollution and biodiversity loss. The governance analysis uncovers institutional fragmentation, implementation gaps, and limited stakeholder engagement, particularly among local communities. Drawing from Japan’s experience in integrated coastal management and disaster preparedness, while acknowledging cultural and socio-political differences, we propose strategic recommendations to enhance the Delta’s resilience. These include establishing a Central Environmental Coordination Committee, developing Community Environmental Councils, and implementing an enhanced policy cycle that integrates both structural and non-structural measures. This research contributes to understanding environmental governance in vulnerable delta regions while offering practical insights for policymakers. The findings emphasize the importance of adaptive, inclusive, and context-specific governance structures in addressing environmental vulnerabilities amid climate change and developmental pressures.